Local-Digital Business Communication Model for Kualuh Traditional Culinary SMEs in North Labuhanbatu Regency - Meylia Arifah Salsa; Kasron Nasution (Ali Institute of Research and Publication, 2026)
This study aims to formulate a local-digital business communication model for traditional culinary SMEs in Kualuh, North Labuhanbatu Regency. The study examines how local-based business communication practices are implemented and how digital communication is understood and utilized by culinary entrepreneurs in supporting business competitiveness. This research employed a qualitative approach with a descriptive-applied method. Data were collected through observation, in-depth interviews, and documentation involving three culinary SMEs, namely Pak Gunawan Restaurant, Kualuh Specialty Restaurant, and Zahira Restaurant. The findings indicate that business communication practices are still dominated by direct interpersonal communication that emphasizes local wisdom values such as friendliness, politeness, hospitality, and quality service. Promotional activities mainly rely on word-of-mouth communication, which remains effective in building customer trust and loyalty. However, the utilization of digital media for business communication and promotion has not yet been optimized due to limited digital literacy and the persistence of conventional communication practices. This study formulates a local-digital business communication model that integrates interpersonal communication based on local cultural values with digital media utilization as a strategy to strengthen competitiveness and maintain the cultural identity of local culinary businesses. The study contributes practically by providing an adaptive communication framework for culinary SMEs in developing market reach without neglecting local wisdom values.